Prince of the Orient : ancient near eastern studies in memory of H.I.H. Prince Takahito Mikasa / edited by Ichiro Nakata, Yoshihiro Nishiaki, Takahiro Odaka, Masamichi Yamada and Shigeo Yamada. (Tokyo)
viii, 272 s.